In Vitro Anti-inflammatory Effects of Equisetum arvense Are Not Solely Mediated by Silica - Steinborn, Carmen; Potterat, Olivier; Meyer, Ulrich; Trittler, Rainer; Stadlbauer, Sven; Huber, Roman; Gründemann, Carsten (Planta Medica, 2018)
Equisetum arvense, known as common horsetail, is used for the treatment of inflammatory diseases and is the plant with the highest concentration of silica. Yet it is unknown if the medicinal properties are mediated by its silica content. In the current study, optimal conditions for silica-rich horsetail preparations were identified. Bioactivity of the preparations was analyzed in vitro using flow cytometry-based activity and functionality profiling of primary human lymphocytes as well as cytokine measurement using a classical ELISA technique. Experiments revealed that horsetail preparations suppress activation and proliferation of lymphocytes by an interleukin-2-dependent mechanism. The effect increased with the silica concentration in the decoctions. Lymphocytesʼ polyfunctionality was also influenced, shown by a downregulation of IFN-γ. Analytical profiling by HPLC-UV-MS and bioactivity testing revealed relevant immunosuppressive concentrations of a component that has been identified as isoquercitrin. Our results show that both silica and isoquercitrin are active compounds of horsetail preparations.
Keywords: Equisetum arvense; Equisetaceae; silica; isoquercitrin; lymphocytes; immune modulation